Seven Guiding Principles for Building Fellowship in SoTL - Acai, Anita; Frake, Mandy; Hamilton, Melanie; Maher, Patrick; Verwoord, Roselynn; Woolmer, Cherie (The Canadian journal for the scholarship of teaching and learning, 2024)
Considering the expansive context of the international Scholarship of Teaching and Learning (SoTL) community, SoTL scholars may wish to reflect and identify what exists for building and nurturing fellowship, and how they may be enacted in practice to benefit others. In this reflective article, we draw on our experiences as International Society for the Scholarship of Teaching and Learning (ISSOTL) Fellows to offer seven guiding principles for building fellowship. These principles include: (1) create space, (2) avoid and resist formal roles, (3) maintain confidentiality and build trust, (4) allow members to self-determine their level of engagement, (5) embrace a group process that is emergent and organic, (6) find congruence in values, and (7) acknowledge the evolutionary nature of the collective. When considered as a meaningful process of community building and engagement, these principles may be useful points of discussion, reflection, and as Felten (2013) states in relation to his Principles for Good Practices in SoTL, to “...articulate a vision of scholarship that enhances, perhaps even transforms, teaching and learning in higher education” (p. 121). Much like Felten, our objective was not to craft a detailed, step-by-step guide for fellowship. Instead, we have provided a series of reference points intended to help people clarify and demystify their own SoTL communities and networks, whether these communities are formal or informal in nature. Compte tenu du vaste contexte de la communauté internationale pour l’avancement des connaissances en enseignement et en apprentissage (ACEA), les chercheurs en ACEA peuvent souhaiter réfléchir et identifier ce qui existe pour construire et nourrir la fraternité, et comment ceci peut être mis en pratique pour en faire bénéficier les autres. Dans cet article de réflexion, nous nous appuyons sur nos expériences en tant que membres de la Société internationale pour l’avancement des connaissances en enseignement et en apprentissage (ISSOTL) pour proposer sept principes directeurs pour développer la fraternité. Ces principes sont les suivants : (1) créer un espace, (2) éviter les rôles formels et y résister, (3) maintenir la confidentialité et établir la confiance, (4) permettre aux membres de déterminer eux-mêmes leur niveau d'engagement, (5) adopter un processus de groupe émergent et organique, (6) trouver une congruence dans les valeurs, et (7) reconnaître la nature évolutive du collectif. Quand on les considère comme un processus significatif de construction et d'engagement de la communauté, ces principes peuvent constituer des points de discussion et de réflexion utiles et, comme l'affirme Felten (2013) à propos de ses principes de bonnes pratiques en matière d’ACEA, « ... articuler une vision de la recherche qui améliore, voire transforme, l'enseignement et l'apprentissage dans l'enseignement supérieur » (p. 121). Tout comme Felten, notre objectif n'était pas de rédiger un guide détaillé, étape par étape, pour établir une fraternité. Au lieu de cela, nous avons fourni une série de points de référence destinés à aider les gens à clarifier et à démystifier leurs propres communautés et leurs propres réseaux d’ACEA, que ces communautés soient de nature formelle ou informelle.